The Influence of Science Comic Based Character Education on Understanding the Concept and Students’ Environmental Caring Attitude on Global Warming Material - Munawwaroh, Eka Lailatul; Priyono, Bambang; Ningsih, Margareta Rahayu (FMIPA UNNES, 2018)
The objective of the study was to determine the effect of the science comic based character education on understanding the concept and students’ environmental caring attitude to the material of global warming. Type research true experimental design with posttest-only control design. The research population was the students of class VII of SMP Negeri 1 Mungkid. The sample was taken by purposive sampling technique consist of class VII H a control class and class VII G an experiment class. The result of the research showed that the study of the students of Class VII of SMP Negeri 1 Mungkid on global warming material reaches completeness equal to 71.42%. The attitude of environmental care of students of Class VII of SMP Negeri 1 Mungkid after using science comic media on global warming material is in the category of very care and care. The implementation of science learning of global warming material of students of Class VII of SMP Negeri 1 Mungkid is done well by 95%. This is supported by the responses of teachers and students who respond well to learning using the science-based science comic media character applied to global warming materials. Based on the results of the study concluded that learning using science comic media based on character education applied to global warming material positively influence the understanding of concept and attitude of environment care of students SMP Negeri 1 Mungkid.